Expression of Hoxa10 Gene in Women with Endometriosis: A Systematic Review - Nurunnajah Lazim; Marjanu Hikmah Elias; Zulazmi Sutaji; Abdul Kadir Abdul Karim; Mohammad Azrai Abu; Azizah Ugusman; Saiful Effendi Syafruddin; Mohd Helmy Mokhtar; Mohd Faizal Ahmad (MDPI, 2024)
Indexed by WOS/Scopus/ERA